(untitled) (Revista Educação, Artes e Inclusão, 2025)
The present work stems from an artistic-educative installation-performance on Dancing at a private university in the state of Rio Grande do Sul, Brazil, focused on the theme of violence against women. It was sought to analyze from the perspective of seven psychology academics and interpreter-creators from the project, how practices based on a performative pedagogy in Dancing can contribute for a critical, sensible and committed University education. For the creative process, visual, auditory, tactile stimuli, contemporary dance techniques and daily records of the experience were used. The learning achieved in this process made it possible to build bodies capable of breaking personal limits, and allowing appropriation from its ability to transform, also strengthening the concept of collectivity and the enjoyment in coexisting. Occupying the university space, in order to cause clefts in it, proved to be a problematizing pedagogy, crossed by experience. Likewise, the break with the structural male chauvinism materialized in the desire to participate in the construction of a different society for women. Thereby, the theoretical concepts explored in class were embodied and went beyond the walls bringing with it the political place of the body when the interpreter-creators begin to take over the university from another place: the place of the complaint, of the protagonism, of the struggle and achievement.